1995
DOI: 10.1520/gtj10330j
|View full text |Cite
|
Sign up to set email alerts
|

A Pluvial Deposition Method to Reconstitute Well-Graded Sand Specimens

Abstract: Stationary pluviators generally use one or more sieves to spread the sand flow exiting from the hopper through one or more holes over the desired area. On the other hand, traveling pluviators do not need a sieve or mesh because in this case it is possible to move an opening or a nozzle over the area of interest. Traveling pluviators are preferable to stationary pluviators, especially in the case of well-graded cohesionless soils, because they provide more uniform specimens. However, traveling pluviators have d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(11 citation statements)
references
References 3 publications
1
9
0
Order By: Relevance
“…The use of this method for obtaining the required relative density has been reported by many researchers [9][10][11]. By using the raining technique, any density within the maximum/minimum density range can be achieved by controlling the intensity and the height of fall of the sand [12][13][14].…”
Section: Test Set Upmentioning
confidence: 99%
“…The use of this method for obtaining the required relative density has been reported by many researchers [9][10][11]. By using the raining technique, any density within the maximum/minimum density range can be achieved by controlling the intensity and the height of fall of the sand [12][13][14].…”
Section: Test Set Upmentioning
confidence: 99%
“…There are three methods for preparation of reconstituted sand specimens, tamping, vibration, and pluviation (Lo Presti et al 1992;ASTM 2006). Among these methods, pluviation has been widely used due to its ability to achieve a wide range of relative densities for sand bed (Rad and Tumay 1987;Fretti et al 1995;Choi et al 2010; Dave and Dasaka 2012;Gade and Dasaka 2015). Additionally, this method is mainly advantageous when it is needed to reconstitute large specimens for model tests or calibration chamber tests within a short time (Fretti et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Among these methods, pluviation has been widely used due to its ability to achieve a wide range of relative densities for sand bed (Rad and Tumay 1987;Fretti et al 1995;Choi et al 2010; Dave and Dasaka 2012;Gade and Dasaka 2015). Additionally, this method is mainly advantageous when it is needed to reconstitute large specimens for model tests or calibration chamber tests within a short time (Fretti et al 1995). Kuerbis and Vaid (1988) reported that the method used to prepare a reconstituted sand bed should be able to produce a very loose to very dense bed, a uniform void ratio throughout the specimen, no segregation of soil particles (regardless of particle size or fines content), and replicable natural soil deposits.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations